In vitro cytotoxicity analysis of doxorubicin-loaded/superparamagnetic iron oxide colloidal nanoassemblies on MCF7 and NIH3T3 cell lines - Tomankova, Katerina; Polakova, Katerina; Pizova, Klara; Binder, Svatopluk; Havrdova, Marketa; Kolarova, Mary; Kriegova, Eva; Zapletalova, Jana; Malina, Lukas; Horakova, Jana; Malohlava, Jakub; Kolokithas-Ntoukas, Argiris; et al. (International journal of nanomedicine, 2015)
One of the promising strategies for improvement of cancer treatment is based on magnetic drug delivery systems, thus avoiding side effects of standard chemotherapies. Superparamagnetic iron oxide (SPIO) nanoparticles have ideal properties to become a targeted magnetic drug delivery contrast probes, named theranostics. We worked with SPIO condensed colloidal nanocrystal clusters (MagAlg) prepared through a new soft biomineralization route in the presence of alginate as the polymeric shell and loaded with doxorubicin (DOX). The aim of this work was to study the in vitro cytotoxicity of these new MagAlg-DOX systems on mouse fibroblast and breast carcinoma cell lines. For proper analysis and understanding of cell behavior after administration of MagAlg-DOX compared with free DOX, a complex set of in vitro tests, including production of reactive oxygen species, comet assay, cell cycle determination, gene expression, and cellular uptake, were utilized. It was found that the cytotoxic effect of MagAlg-DOX system is delayed compared to free DOX in both cell lines. This was attributed to the different mechanism of internalization of DOX and MagAlg-DOX into the cells, together with the fact that the drug is strongly bound on the drug nanocarriers. We discovered that nanoparticles can attenuate or even inhibit the effect of DOX, particularly in the tumor MCF7 cell line. This is a first comprehensive study on the cytotoxic effect of DOX-loaded SPIO compared with free DOX on healthy and cancer cell lines, as well as on the induced changes in gene expression.
Keywords: Cell Survival; DOX/SPIO nanocarriers; MFC-7 buňky; Humans; doxorubicin; Antineoplastic Agents; Doxorubicin; in vitro cytotoxicity; lidé; zvířata; myši; buňky NIH 3T3; Mice; NIH 3T3 Cells; Colloids; koloidy; protinádorové látky; superparamagnetic iron oxide nanoparticles; magnetické nanočástice; Animals; Magnetite Nanoparticles; viabilita buněk; MCF-7 Cells